Peer Review of Radiotherapy Planning: Quantifying Outcomes and a Proposal for Prospective Data Collection. Issue 12 (December 2016) - Mackenzie, J.; Graham, G.; Olivotto, I.A.
Abstract: Aims: The Canadian Partnership for Quality Radiotherapy quality assurance guidelines recommend that radiation oncologist peer review of curative radiotherapy plans takes place ideally before the first fraction of treatment is delivered. This study documented and evaluated the outcomes of weekly, disease site-specific, radiotherapy peer review, quality assurance rounds at the Tom Baker Cancer Centre in Calgary, Canada with a view to making recommendations about the optimal timing and documentation of peer review during the radiotherapy planning processes. Materials and Methods: Outcomes of each case reviewed at (i) breast, (ii) head and neck (including thyroid and cutaneous cases) and (iii) lung team quality assurance rounds from 6 January to 5 May 2015 were recorded prospectively. Each radiotherapy plan was assigned an outcome: A for plans with no suggested changes; B for satisfactory, but where issues were raised to consider for future patients; or C when a change was recommended before the first or next fraction. The B outcomes were further subdivided into B1 for a case-specific concern and B2 for a policy gap. Plans were assessed after contour definition and before the plan was formulated (post-contouring reviews) and/or assessed when the plan was complete (post-planning reviews). Results: 209 radiotherapy plans prescribed by 20 radiation oncologists were peer reviewed at 43 quality assurance meetings. 93% were curative-intent and 7% were palliative. 83% of plans were reviewed before delivery of the first treatment fraction. There were a total of 257 case reviews: 60 at the post-contouring stage, 197 at the post-planning stage, including 46 patients reviewed at both time points. Overall rates of A, B1, B2 and C outcomes were 78%, 9%, 4% and 9%, respectively. The most common reason for a B or C outcome was related to target volume definition. Only 56% of C outcomes at the post-planning stage would have been detected at the post-contouring stage. Results varied between tumour site groups. Conclusions: 9% of radiotherapy plans reviewed had changes suggested before delivery to the patient. Review at the post-planning stage after plan completion was necessary to detect all suggested changes, but for head and neck cases, all C outcomes could have been detected at the post-contouring stage. More widespread implementation of radiotherapy peer review in the UK is recommended. Highlights: Weekly radiotherapy quality assurance meetings were audited for breast, lung and head and neck tumour sites. In 9% of cases, peer review recommended immediate changes in the radiotherapy treatment plan. A nomenclature was developed to categorise and document the outcome of peer review. Results show strengths of peer review in maintaining high standards of radiotherapy delivery.